P2-S2.10 Sex worker collective organization in the absence of NGOs: a qualitative analysis of female sex worker hometown social networks in South China. (10th July 2011) - Tucker, J; Peng, H; Wang, K; Chang, H; Yang, L G; Zhang, S; Yang, B
Abstract : Background: Reducing harm associated with selling and purchasing sex is an important public health priority in China, yet there are few examples of sustainable, successful programs to promote sexual health among female sex workers. Programs focusing on empowering sex workers using a rights-based framework have been effective in India and other regions, but have been challenging to replicate in China. The limited civil society and scope of nongovernmental organizations circumscribe the local capacity of female sex workers to collectively organise, advocate for their rights, and implement STI/HIV prevention programs. The purpose of this study was to examine social networks among low-income female sex workers in South China to determine their potential for sexual health promotion. Methods: Semi-structured interviews with 34 low-income female sex workers and 28 outreach members were used to examine how social relationships affected condom use and negotiation, STI/HIV testing and health-seeking behaviours, and dealing with violent clients. Results: These data showed that sex worker's hometown social connections were more powerful than relationships between women selling sex at the same venue in establishing the terms and risk of commercial sex. Female sex workers from the same hometown often migrated to the city with their hometown sisters and these social connections fulfilled many of the functions of non-governmental organizations, including collective mobilisation, condom promotion, violence mitigation, and promotion of health-seeking behaviours. Outreach members observed that sex workers accompanied by their hometown sisters were often more willing to accept STI/HIV testing and trust local sexual health services. Conclusions: Organising STI/HIV prevention services around an explicitly defined hometown social network may provide a strong foundation for sex worker health programs. Further research on dyadic interpersonal relationships between low-income female sex workers, group dynamics and norm establishment, and the social network characteristics are needed. Hometown social networks may represent a powerful force for organising STI/HIV prevention among low-income sex workers in China and other regions with limited civil society.